Point Mutations and Antiviral Drug Resistance - Arellano-Galindo, José; Barron, Blanca Lilia; Vargas-Infante, Yetlanezi; Santos-Esteban, Enrique; Herrera-Martinez, Emma del Carmen; Velazquez-Guadarrama, Norma; Reyes-Teran, Gustavo (IntechOpen, 2012)
None